Description of dynamic images: a systematic mapping for the understanding and transparency of information that may be perceptible visually impaired citizens - Marques, João Marcelo dos Santos; Ferreira, Simone Bacellar Leal (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: With the advent of the Web and the advancement of information and communication technologies (ICTs), society began to keep itself informed of facts and everyday events and can be connected anywhere on the planet. However, a portion of society, such as the visually impaired, still face major challenges in Information Systems (IS) on the Web regarding access to information in dynamic images. Problem: These citizens, in general, cannot understand the information described in these images, so that they can build a mental model. You need to provide alternative ways of describing them. Solution: In this article, studies were explored that could help in the description of dynamic images under the pillars of understanding, transparency of information and perception for the construction of SIs for the visually impaired. SI theory: This work follows the protocols adopted for systematic mapping directed to meta-analysis and hermeneutics. Method: A Systematic Mapping of the Literature was used following the steps of planning, conducting and analyzing the results. Summary Results: From the search repositories, 1019 studies were captured. After applying the evaluation criteria, 11 relevant studies were accepted. The results revealed that there are few studies in the development of technologies that use methods, models and techniques for the description of dynamic images. Contributions to IS: As a contribution, this work exposes research gaps for the creation of ISs that include descriptions in dynamic images for the understanding and transparency of perceptible information to people with visual impairments. In addition to instigating research in Human-Computer Interaction aligned with the GranDSI-BR 2016-2026.